Respuesta :
Answer:
x= -3
Step-by-step explanation:
3(x-4)= -21
x - 4 = -7( to get this divide both sides of the equation by 3 )
x = -7 + 4 ( add 4 to both sides of the equation)
x = -3 ( then add -7 and 4 to get -3)
So clearly x = -3
HOPE THIS HELPED
HERE IS YOUR ANSWER
3(x-4)= -21
=3x-12=-21
=3x= -21+12
=3x= -9
= x= -9/3
=x= -3
DONT FORGET TO MARK BRAINLIEST AND HIT THE LIK.. man I’m just kidding
3(x-4)= -21
=3x-12=-21
=3x= -21+12
=3x= -9
= x= -9/3
=x= -3
DONT FORGET TO MARK BRAINLIEST AND HIT THE LIK.. man I’m just kidding